INDIVIDUALIZATION OF RIGHTS ON PURA PROFIT LAND - Cokorda Gede Ramaputra; I Made Suwitra; Luh Putu Sudini (Warmadewa Press, 2019)
This research aims is to analyze the validity of the transfer of land rights Pura profit in the perspective of legal certainty and protection of the law in the conservation of land Pura profit in Badung regency. This research is an empirical law study using primary data and secondary data. An Approach used in the form of the approach of legislation analysis, case and custom law. Based on the results of the research can be analyzed that the sale and purchase of land Pura profit executed after the fulfilled special terms and general terms according to the customary law and law of the country. The purpose is for the legal certainty and legal protection for both the buyer and the existence of the temple itself. Therefore, for Pura profit is expected to be innovatively able to manage temple income to be useful to support the activities of temple balance.